2021
DOI: 10.1002/cbf.3650
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biophysical stimulation on osteogenic differentiation and the mechanisms from ncRNAs

Abstract: Ample proof showed that non-coding RNAs (ncRNAs) play a crucial role in proliferation and differentiation of osteoblasts and bone marrow stromal cells (BMSCs). Varied forms of biophysical stimuli like mechanical strain, fluid shear stress (FSS), microgravity and vibration are verified to regulate ncRNAs expression in osteogenic differentiation and influence the expression of target genes associated with osteogenic differentiation and ultimately regulate bone formation. The consequences of biophysical stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…Previous studies showed that mechanical stimuli induce intramembranous and endochondral ossification, and promote fracture healing [49]. In addition, biophysical stimuli such as mechanical strain, fluid shear stress (FSS), microgravity and vibration regulate non-coding RNA expression, thereby regulating the process of osteogenic differentiation [50,51]. Piezo1 as a major mechanosensor is necessary for mechanical stimulation to promote bone formation [21,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that mechanical stimuli induce intramembranous and endochondral ossification, and promote fracture healing [49]. In addition, biophysical stimuli such as mechanical strain, fluid shear stress (FSS), microgravity and vibration regulate non-coding RNA expression, thereby regulating the process of osteogenic differentiation [50,51]. Piezo1 as a major mechanosensor is necessary for mechanical stimulation to promote bone formation [21,50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biophysical stimuli such as mechanical strain, fluid shear stress (FSS), microgravity and vibration regulate non-coding RNA expression, thereby regulating the process of osteogenic differentiation [50,51]. Piezo1 as a major mechanosensor is necessary for mechanical stimulation to promote bone formation [21,50]. Therefore, Piezo1 can act as a promising therapeutic target to promote fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Li et al [ 34 ], lncRNA-H19 sponging miRNA-141 could modulate osteogenesis in nude mice models as well as in stem cells from apical papilla cultured in vitro . Interestingly, the expression of noncoding RNAs during osteogenic differentiation can be regulated by different biophysical stimuli, such as mechanical strain, fluid shear stress, or microgravity, followed by upregulation or downregulation of osteoblast differentiation-related genes [ 11 ]. Additionally, increasing evidence has demonstrated that osteogenic differentiation of MSCs can be genetically manipulated by various transcription factors, such as myocardin-related transcription factor A [ 35 ], zinc finger E-box-binding homeobox 1 [ 36 ], and T-Box20 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, hDPSCs have been reported to exhibit a similar or even higher osteogenic potential compared with bone marrow mesenchymal stem cells (BMSCs) [6][7][8][9]. Numerous previous studies have reported that the osteogenic capacity of MSCs can be regulated by many factors [10,11], including noncoding RNA, transcription factors, bioactive materials, and various different biophysical stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant evidence that non‐coding RNA plays a crucial role in the proliferation and differentiation of osteoblasts and bone marrow stromal cells. 40 For example, LncRNA HOTTIP accelerates osteogenic differentiation by interacting with TAF15 to stabilize DLX2. 41 LncRNA KCNQ1OT1 promotes osteogenic differentiation through miR‐205‐5p/RICTOR axis.…”
Section: Discussionmentioning
confidence: 99%